Concordance between 13C:12C ratio technique respect to indirect calorimetry to estimate carbohydrate and Fat oxidation rates by means stoichiometric equations during exercise. A reliability and agreement study - González‐Haro, Carlos (Physiological reports, 2019)
Indirect calorimetry is a tool used routinely by sport/exercise physiologist to assess the metabolic response to training and to nutritional interventions. There are different stoichiometric equations to estimate fat (FatOxR) and carbohydrates (CHOOxR) oxidation rates, however there are not enough information in literature about what are the most accurate equations. The purpose of this study was to determine the concordance between indirect calorimetry and a method of reference for stoichiometric equations used to estimate FatOxR and CHOOxR. Concordance between indirect calorimetry and the method of reference (13C to 12C ratio (13C:12C ratio) technique) for key stoichiometric equations was assessed in well‐trained triathletes. Subjects carried out a carbohydrate depletion‐repletion protocol, labeling the glycogen stores with 13C, and a laboratory test to assess the 13C metabolic response during a wide range of aerobic intensities during exercise. All the equations showed a narrow agreement interval (Δ) (CHOOxR nPC (protein component negligible): −0.308, 0.308, CHOOxR PC (protein component): −0.268, 0.268, FatOxR nPC and PC: −0.032, 0.032 (g·min−1)). FatOxR showed a similar concordance (28–32%) with CHOOxR nPC ranging from 55% to 75%, and for CHOOxR PC between 51% to 71%. None of the stoichiometric equations met a perfect agreement with the method of reference. The Jeukendrup and Wallis equation showed the best concordance for CHOOxR nPC whilst the Frayn and Ferrannini (Glu) equations had the best agreement for CHOOxR PC. All FatOxR equations showed similar concordances and they are able to be used indistinctly. When FatOxR and CHOOxR are measured by means indirect calorimetry and compared to the method of reference, all FatOxR equations showed similar concordances and they are able to be used indistinctly. For CHOOxR the Jeukendrup and Wallis equation shows the best concordance, when the protein component is not taken into account (nPC), whilst the Frayn, and Ferrannini (Glu) equations has the best agreement when the protein component (PC) is considered.